Entrepreneurial Progress: Climbing The Entrepreneurial Ladder in Europe and The US - Peter van der Zwan; Ingrid Verheul; Roy Thurik; Isabel Grilo (Tinbergen Institute, 2009)
We investigate which countries have the highest potential to achieve entrepreneurial progress. This progress is defined using an entrepreneurial ladder with five successive steps: “never thought about starting a business”, “thinking about starting a business”, “taking steps to start a business”, “running a business for less than three years”, and “running a business for more than three years”. We assess the influence of individual-level and country-level variables on progression through these stages. Data are used from the 2007 “Flash Eurobarometer Survey on Entrepreneurship”, covering 27 European countries and the United States. We find that countries display large variation in the ease with which businesses come into existence and survive. In the US many people think about setting up a business whereas Europeans are better at achieving higher levels of engagement. Particularly in Austria, France and Lithuania there appear to be low probabilities to advance in the process. Our analysis suggests that country differences can be explained by the level of economic development and risk tolerance while the administrative and financial climate play a role for some steps. The paper also provides results on the influence of individual-level demographic and obstacle perception variables.
Keywords: H10; J23; L26; M13; R12; 330; entrepreneurship; determinants; nascent entrepreneurship; competitiveness; continuation ratio logit; Entrepreneurship-Ansatz; Erfolgsfaktor; Unternehmensgründung; Unternehmenserfolg; Europa; USA